Student Character Building via Al-Quran-Based Pedagogical Models - Fikri Aldi (Sufiya Journal of Islamic Studies, 2023)
Abstract Developing strong Islamic character among students has become a major challenge for Islamic educational institutions in the contemporary era. This study employed a library research approach by collecting data from journal articles, books, theses, and empirical implementations of Islamic education, which were then analyzed descriptively and systematically to construct a conceptual model of Qur’an-based character education. The findings reveal that Qur’an-based education offers a holistic paradigm for instilling moral values through the integration of advisory guidance (mau‘izhah), exemplary conduct (uswatun hasanah), habituation (ta‘wid), and reward-punishment strategies (targhib and tarhib). The analysis further indicates that synergy among teachers, parents, students, and the school environment constitutes the key factor in the successful internalization of moral values, while simultaneously minimizing problems related to fragmented methods, limited facilities, and inconsistencies in educators’ roles. The implementation of this model not only strengthens the formation of Islamic behavior but also provides a conceptual framework for educational institutions in designing effective curricula and learning strategies. The study implies that Qur’an-based character education can serve as a strategic foundation for cultivating a generation that is morally upright, disciplined, honest, and responsible, in accordance with the principles of character education from an Islamic perspective.